Non‐communicable disease (NCD) risk among people living with HIV in KwaZulu‐Natal, South Africa: evidence from a randomised trial of community‐based differentiated service delivery - Maitreyi Sahu; Adam A. Szpiro; Heidi vanRooyen; Stephen Asiimwe; Maryam Shahmanesh; D. Allen Roberts; Meighan L. Krows; Kombi Sausi; Nsika Sithole; Torin Schaafsma; Jared M. Baeten; Adrienne E. Shapiro; et al. (Journal of the International AIDS Society, 2025)
Abstract Introduction As differentiated HIV services provided outside of clinics are scaled up, clients may have fewer interactions with ancillary services for non‐communicable disease (NCD) prevention and management traditionally offered within facilities. This study was embedded in the DO ART randomised trial (2016−2019), which demonstrated that community‐based differentiated service delivery (DSD) improved HIV viral suppression compared with facility‐based care. We assessed NCD risk among men and women living with HIV accessing community‐based DSD versus facility‐based care in KwaZulu‐Natal, South Africa. Methods First, we described lifestyle and clinical NCD risk among DO ART participants in rural and semi‐rural KwaZulu‐Natal. Next, we compared clinical NCD risk at 12 months by randomisation arm (community‐based DSD vs. facility‐based care). Finally, we explored the relationship between 12‐month viral suppression and clinical NCD risk, overall and stratified by randomisation arm (i.e. service delivery type). Results Among 1010 participants, the median age was 32 years, 245 (24%) smoked, 229 (23%) had hypertension and 502 (50%) were overweight or obese (body mass index [BMI] ≥ 25). Smoking was more common among men than women (43% vs. 6%, p ≤ 0.001), while overweight/obesity was more common among women than men (65% vs. 34%, p ≤ 0.001). We found no statistically significant association between service delivery type and clinical NCD risk factors at 1 year. We also found no significant associations between viral suppression at 12 months and blood pressure, haemoglobin A1c or smoking. However, virally suppressed clients had higher mean BMI (+0.93 kg/m2, p = 0.004) and higher mean cholesterol (+5.79 mg/dl, p = 0.001). These associations were greater in effect size and statistically significant among clients receiving community‐based DSD (BMI: p = 0.003; cholesterol: p = 0.001), but smaller and not significant for facility‐based care (BMI: p = 0.299; cholesterol: p = 0.448). Conclusions Relatively younger adults accessing HIV treatment in South Africa had substantial NCD risk, which differed by gender and may increase with age. Among clients receiving community‐based DSD, viral suppression was associated with modestly higher BMI and cholesterol levels. Community‐based DSD programmes should consider integrating NCD risk screening and management that addresses gender‐specific needs to prevent premature mortality among people living with HIV. Clinical Trial Number NCT0292999